ELECTRICAL AND NOISE PROPERTIES OF A SYMMETRICAL ANTENNA WITH AN ACTIVE BALUN - Tokarsky, P. (Radio physics and radio astronomy (Print), 2025)
Subject and Purpose. The paper considers an active receiving antenna composed of a symmetrical passive antenna and an active balun that consists of a diff erential pair of identical low-noise amplifiers and a three-winding differential-input single-ended transformer. The purpose of the paper is developing a model of such an active antenna in the form of an equivalent two-port network with analytically determined electrical and noise parameters. Methods and Methodology. The study is based on methods of antenna theory and noise theory of multi-port networks. The passive antenna is conditionally divided into two identical arms, each regarded as a separate independent antenna, which allows representing the entire active antenna as a three-port network. Then, making allowance for the antisymmetric excitation of the three-port network inputs, it has been converted into a cascade of two two-port networks. The first one corresponds to the passive antenna, and the second to the active balun consisting of one low-noise amplifier with transformers added at input and output . Results. Proceeding from a block diagram of the active antenna, seen as a two-port network, analytical expressions were derived to allow calculations of its scattering matrix and the correlation matrix of noise waves. These permit evaluating electrical and noise parameters of the symmetrical antenna with an active balun. A numerical example is presented, which allows comparing parameters of two symmetrical active antennas, one of which uses the active balun, while the other a low-noise amplifier with a passive balun. Conclusions. The block diagrams developed and the explicit relationships obtained allow a greatly simplified analysis of the symmetric antennas that employ active baluns as they do not need resorting to any specialized software. The results may prove useful for calculating the parameters of low-frequency radio telescopes that employ similar antennas in the capacity of phased array elements.